2023
DOI: 10.1057/s41270-023-00230-w
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing mobile in-app advertising effectiveness using app publishers-controlled factors

Abstract: Mobile in-app advertising has become one of the most popular business advertising platforms in recent years. This relatively new advertising strategy’s annual spending has increased dramatically in recent years. Despite its practical success, the background theory for mobile in-app advertising is still in its infancy. This type of advertising also sees the emergence of new participants, such as ad networks and app publishers, which leads to the development of new theoretical constructs and more nuanced concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…The influence of antecedents such as advertisement types affects the click-through rate (Rosenkrans and Myers, 2018), advertising avoidance behaviors (Keem and Lee, 2018), purchase intention (Sung, 2021) and social media sharing (Sung et al ,2022). The interactive effects of publisher-controlled factors, namely, ad space size, ad space position ad space timing (Truong et al , 2019), and ad space duration (Truong, 2023), with advertiser-controlled factors, namely, ad type, ad medium, location (Truong et al , 2019) and time (Truong, 2023), on the click-through rate were investigated. Wang and Chou (2019) examine how the degree of congruity between promoted products in interstitial ads and the app environment affects consumer response toward the ad.…”
Section: Theory-context-characteristics-methodology In In-app Adverti...mentioning
confidence: 99%
See 3 more Smart Citations
“…The influence of antecedents such as advertisement types affects the click-through rate (Rosenkrans and Myers, 2018), advertising avoidance behaviors (Keem and Lee, 2018), purchase intention (Sung, 2021) and social media sharing (Sung et al ,2022). The interactive effects of publisher-controlled factors, namely, ad space size, ad space position ad space timing (Truong et al , 2019), and ad space duration (Truong, 2023), with advertiser-controlled factors, namely, ad type, ad medium, location (Truong et al , 2019) and time (Truong, 2023), on the click-through rate were investigated. Wang and Chou (2019) examine how the degree of congruity between promoted products in interstitial ads and the app environment affects consumer response toward the ad.…”
Section: Theory-context-characteristics-methodology In In-app Adverti...mentioning
confidence: 99%
“…Publishers can either sell their inventory directly to ad networks or buy-side or engage in real-time bidding (Kaplan, 2021). Truong (2023) found that the optimal combination of publisher-controlled factors such as duration, timing, size and position of the ad space significantly improves the click-through rate of in-app advertising.…”
Section: Theme 1: Ad Platform Optimizationmentioning
confidence: 97%
See 2 more Smart Citations